Research on the Design of Interactive Children's Vocal Enlightenment Toys Based on Audiovisual Association Experience. - Bai, Quan (Occupational Therapy International, 2022)
This paper examines the characteristics and current situation of children's vocal enlightenment toy design, studies how to design children's verbal enlightenment toys based on audiovisual associative experience, and develops appropriate optimization strategies and approaches. This paper analyzes the theoretical basis involved in design practice, summarizes the generation and concept of audiovisual association and the significance of associative experience for children's vocal enlightenment, explores the application and characteristics of interaction design in children's toys, and summarizes the creation of interactive toys. The triggered form of associative experience is determined according to the physical and mental development characteristics, interaction behavior, and experimental research of children at this stage. By summarizing the typical design elements of existing children's interactive toys with good sales and reputation and designing a questionnaire, the Kano model was used to obtain the design element priorities to guide design practice. We used audiovisual association as an entry point to writing a sound and picture interactive program through processing and the Arduino platform to develop the interactive toys. "Sound fun" is an interactive toy that extracts the characteristics of children's voices to correspond to the changes of picture elements and can provide real-time feedback of dynamic pictures through the user's voice to achieve the purpose of triggering a synesthetic experience. Interaction design applied to toy design is a new direction in terms of traditional toy design, which enhances the interactivity of toys and enhances the user's sense of experience and participation in the use of toys; it can improve the affinity and fun of toys.